Mechanism for Controlling Access to Private Information at the Cellular Level (Indo-American Journal of Life Sciences and Biotechnology, 2016)
A suitable testing strategy for service-orientedapplications will be implemented in this project. Andboost the efficiency of the online service. In thisarticle, I outline an architecture that can adapt toshifting requirements in terms of service operation,argument types, and service composition. My modelatomic and composite web services undergo randomtesting at runtime as part of the testing system's proofof concept. in order to maintain the testinginfrastructure's availability while a new test subject isbeing configured automatically.